Use of Interactive and Modern Pedagogical Software in the Process of Freelancing Sites in Medicine (Eurasian Scientific Herald, 2023)
Insights into these Freelancer sites and how to use them. Use of interactive and modern pedagogical software tools in the process of freelancing sites education.